Hubungan Koping Keluarga Dengan Kepatuhan Dalam Pengobatan Pada Anggota Keluarga Yang Mengalami Penyakit Tuberkulosis Di Puskesmas Cimanggis Depok: The Relationship Between Family Coping and Compliance with Treatment in Family Members Who Have Tuberculosis Disease at the Cimanggis Community Health Center, Depok - Hayangua, Sintia M. (Dohara POAJ, 2024)
Introduction: Mycobacterium tuberculosis is a disease that has become a health problem at the national and world levels. Mycobacterium tuberculosis has infected one-third of the world's population Pulmonary Tuberculosis disease is a disease that undergoes routine treatment with a period of 6-8 months. Methods: The design of this study is quantitative using a correlation descriptive design. The design to be used in this study is a design to examine the relationship between two variables in a situation or a group of subjects. The population in this study is all families with Tuberculosis disease at the Cimanggis Depok Health Center namely 30 family members. Sampling technique using Accidental Sampling. Results: Based on the chi-square result of respondents who did maladaptive family coping and adherence in non-adherent treatment were 13 (76,5%) while respondents who did adaptive family coping and adherence treatment were 10 (76,9%). The result of the statistical test in the p-value = 0,011 means P < 0,05 then H0 is rejected and Ha is accepted it is concluded that there is a relationship between family coping with adherence in treatment for family members who experience Tuberculosis disease at the Cimanggis Depok Health Center. With an OR value of 10,833 it can be concluded that respondents with adaptive mal family coping are 10,8 times more likely to experience non-compliance than those with adaptive family coping. Discussion: H0 is rejected and Ha is accepted so it is concluded that there is a relationship between family coping adherence to treatment in family members who experience Tuberculosis disease at the Cimanggis Depok Health Center.